First Report of Hematosalpinx in a Cat With a Large Hematoma and Severe Anemia - Teruo Itoh; Atsuko Kojimoto; James Chambers; Kazuyuki Uchida; Hiroki Shii (Case Reports in Veterinary Medicine)
A 6-year-old, intact female cat presented with sudden collapse. Clinical examinations indicated severe regenerative anemia and a large abdominal mass containing fluid. An exploratory laparotomy revealed a large cystic lesion at the cranial end of the right uterine horn. Ovariohysterectomy was performed, and the cat made a full recovery. The cystic lesion contained a blood clot and 102 mL of blood. Histological examination confirmed that the hemorrhagic lesion was located within the fallopian tube. The thickened uterus with severe vasodilation was histologically diagnosed as endometrial hyperplasia with congestion. This is the first reported case of hematosalpinx in a cat, a rare condition previously described in humans.